Political alchemy - Horváth, Ágnes, 1957- author.
1 online resource (vii, 208 pages)
Keywords: "This book explores politics as a form of alchemy, understood as the transformation of entities through an alteration of their identities. Identifying this process as a common denominator of many political phenomena, such as communism, EU integration, mediatisation or globalisation, the author demonstrates not only the widespread presence of alchemical techniques in politics, but also the acceleration of their deployment. A study of the steady growth of power as it reaches a continuous and permanent stage, thus avoiding the inherent difficulties connected with birth and death of political organisations and institutions, this volume reveals political alchemy to be a form of self-sustaining growth through sterile multiplication, devoid of meaning. Revealing both the integrative and disintegrative nature of a political process that, while appearing to work in the interests of all, in fact produces apathy, desperate mobilisation and despair by crushing concrete entities such as personality and tradition, Political Alchemy: Technology Unbounded will appeal to scholars of sociology and anthropology with interests in social theory and political thought"--